STRATEGI PENGEMBANGAN KREATIVITAS ANAK USIA DINI DIMASA PANDEMI - Widyasanti, Ni Putu (Institut Agama Hindu Negeri Gde Pudja Mataram, 2021)
Development in early childhood is marked by changes in behavior and abilities. The development of creativity in early childhood is one of the most important developments to pay attention to. Creativity is a person's interaction with the environment to create methods or products that are imaginative and have benefits for solving problems. Children's creativity is surrounded by unique ideas and the growth of imagination and fantasy. Creative children are sensitive to stimulation. To develop children's creative abilities, strategies are needed that are in accordance with the abilities and situations of early childhood today. The pandemic situation requires teachers to be more creative in designing learning strategies for early childhood. This study aims to determine the strategy of Pelita Sari Kindergarten teachers in developing early childhood creativity during the pandemic. This research method is descriptive qualitative. The results of this study describe the strategies of Pelita Sari Kindergarten teachers in developing early childhood creativity during the pandemic. The strategies used by the teacher are more and consistently use the strategy of developing creativity through creating products (hasta work). Through real work, not only creativity will develop, but cognitive abilities will also be well facilitated. Children will use their imagination to form a certain building or object according to their imagination in craft activities. In their manufacture they use a variety of different materials can use materials that are easily found. Every child is free to express their creativity, so we will get different results from one child to another.